(3GdeNJGQ GdLGeY Hjf GdoefJbi hGdGSJPcGQs - (3eMeO Hf YHO GdMb Hf YHO Gddg GdJdeSGfj,J (B625 (3g` s ((3eMeO Hf bGSe Hf YjSi s)
(3ChdgG (B:s
(3eG LGA ai Scf GdeOjfI hGdNQhL efgG hbhd QShd Gddg Udi Gddg Ydjg hSde (B: (3dGjUHQ Ydi dChGFgG hTOJgG CMO EdG cfJ dg TajYkG jhe GdbjGeI s
(3BNQgG (B:s
(3HeG LGA ai CSeGA GdfHi Udi Gddg Ydjg hSde hBNQ eG ajg (B: (3ajLhR Cf Jbhd Efg YGde heQTO hQTjOhgG heGjLQi eLQCg s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI HGdQHGW (B(176 (3b(B) s
Keywords: (3GdMOjK h GdeUWdMs